Brazilian scientific evidence on Fournier's gangrene - Érick Igor dos Santos; Amanda Luiza Vasconcellos Vertulli Vale; Isabel Cristina Peixoto Marinho dos Reis; Priscila Benevides Neves; Cristiane Marinho Pontes; Sarita Gonçalves de Campos Camara (Universidade Federal do Ceará, 2015)
The objective of this study was to describe the Brazilian scientific reports published over the past twenty years on Fournier's gangrene. It is an integrative review conducted through incursions in the LILACS, MEDLINE, BDENF and Coleciona SUS databases with the descriptor 'Fournier's Gangrene'. Texts published between January 1994 and July 2014, in Portuguese, and freely available online were selected. According to the 14 articles found, the main symptoms of Fournier's gangrene include discomfort with painful sensations, high fever, edema, malaise, and sweating. In most cases erythema and blistering are observed, evolving into a wound. The clinical profile assists in the selection of empirical antimicrobial therapy even before the culture results. It was concluded that early diagnosis and appropriate and aggressive treatment are crucial in patient prognosis. There is still a shortage of Brazilian scientific production with a high power of evidence on the subject.